Severe Infections following Rituximab Treatment in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Zhi-Ying Li; Min Chen; Ming-Hui Zhao (Karger Publishers, 2020)
Introduction: Severe infections were not rare in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) patients treated with rituximab. The current study aimed to evaluate severe infections in AAV patients received rituximab administration in a single Chinese center. Methods: Twenty-seven patients were retrospectively included in this study. Their demographic and clinical data were analyzed. Severe infections were classified as grade ≥3 as proposed by the Common Terminology Criteria for Adverse Events V.4.0. Results: Patients were followed up for 23.6 ± 14.0 months from the time of rituximab initiation (mean rituximab dose 1,270.4 mg). Ten severe infection events were recorded in 10 (37.0%) patients, corresponding to an event rate of 20.9 per 100 person-years. Pulmonary infections were the leading infectious complications (90%). Eight of the 10 infections occurred during the first 12 months of follow-up. In multivariable analysis, severe infection in the first year was independently associated with age (HR: 1.121, 95% CI: 1.011-1.243, p = 0.031) and serum creatinine level (increased by per 88.4 μmol/L; HR: 1.493, 95% CI: 1.017-2.191, p = 0.041). Conclusion: In AAV patients receiving rituximab, severe infections were common even with the low-dose regimen. Pulmonary infections were the leading cause, and most infections occurred during the first 12 months of follow-up. Older age and renal dysfunction were the risk factors for infection.